A VASt-domain protein regulates autophagy, membrane tension, and sterol homeostasis in rice blast fungus. Issue 10 (3rd October 2021) - Zhu, Xue-Ming; Li, Lin; Cai, Ying-Ying; Wu, Xi-Yu; Shi, Huan-Bin; Liang, Shuang; Qu, Ying-Min; Naqvi, Naweed I.; Del Poeta, Maurizio; Dong, Bo; Lin, Fu-Cheng; Liu, Xiao-Hong
ABSTRACT: Sterols are a class of lipids critical for fundamental biological processes and membrane dynamics. These molecules are synthesized in the endoplasmic reticulum (ER) and are transported bi-directionally between the ER and plasma membrane (PM). However, the trafficking mechanism of sterols and their relationship with macroautophagy/autophagy are still poorly understood in the rice blast fungus Magnaporthe oryzae . Here, we identified the VAD1 Analog of StAR-related lipid transfer (VASt) domain-containing protein MoVast1 via co-immunoprecipitation in M. oryzae . Loss of MoVAST1 resulted in conidial defects, impaired appressorium development, and reduced pathogenicity. The MoTor (target of rapamycin in M. oryzae ) activity is inhibited because MoVast1 deletion leads to high levels of sterol accumulation in the PM. Site-directed mutagenesis showed that the 902 T site is essential for localization and function of MoVast1. Through filipin or Flipper-TR staining, autophagic flux detection, MoAtg8 lipidation, and drug sensitivity assays, we uncovered that MoVast1 acts as a novel autophagy inhibition factor that monitors tension in the PM by regulating the sterol content, which in turn modulates the activity of MoTor. Lipidomics and transcriptomics analyses further confirmed that MoVast1 is an important regulator of lipid metabolism and the autophagy pathway. Our results revealed and characterized a novel sterol transfer protein important for M. oryzae pathogenicity. Abbreviations: AmB: amphotericin B; ATMT: Agrobacterium tumefaciens -mediated transformation; CM: complete medium; dpi: days post-inoculation; ER: endoplasmic reticulum; Flipper-TR: fluorescent lipid tension reporter; GO: Gene ontology; hpi: hours post-inoculation; IH: invasive hyphae; KEGG: kyoto encyclopedia of genes and genomes; MoTor: target of rapamycin in Magnaporthe oryzae ; PalmC: palmitoylcarnitine; PM: plasma membrane; SD-N: synthetic defined medium without amino acids and ammonium sulfate; TOR: target of rapamycin; VASt: VAD1 Analog of StAR-related lipid transfer; YFP, yellow fluorescent protein.